Effect of non-invasive brain stimulation on cognitive function and activities of daily living in patients with carbon monoxide poisoning: a systematic review and meta-analysis - Ding, Hui; Wei, Chen; Chen, Jiwei; Yu, Fen; Wang, Xing; Zhang, Yuanwen (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of non-invasive brain stimulation (NIBS) in improving cognitive function and activities of daily living (ADL) in patients with delayed encephalopathy after acute carbon monoxide poisoning (DEACMP). It also sought to explore the moderating effects of age, intervention duration, latency period, and stimulation site.MethodsA systematic search of seven databases was conducted to identify randomized controlled trials (RCTs) published up to August 2024. Meta-analyses and publication bias assessments were performed using RevMan 5.4.1 and Stata 17.0. Methodological quality was evaluated with the PEDro scale, and the certainty of evidence was assessed using GRADEpro.ResultsA total of eight RCTs involving 607 participants were included. The pooled results indicated that NIBS significantly improved cognitive function (standardized mean difference (SMD = 1.03, p < 0.00001) and ADL (SMD = 1.77, p < 0.00001). The subgroup analyses showed greater cognitive improvements in patients aged below 50 years, with intervention durations of ≤20 days and stimulation applied at the yin–yang poles. In contrast, improvements in daily activities were more pronounced in patients aged over 50 years under similar intervention conditions.DiscussionThe included studies were of moderate-to-high quality (mean PEDro score = 6.3). The major limitations included inadequate blinding and incomplete allocation concealment. The heterogeneity observed was mainly attributable to patient age, stimulation site, and intervention duration. No significant publication bias was detected. Overall, NIBS demonstrated moderate-quality evidence in enhancing cognitive function and daily activity performance, with individual characteristics moderating its effects.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024598815.